La météorologie du sensible chez Nina Bouraoui - Loucif Badreddine (Carnets)
Born between two cultures, Western and Eastern, Nina Bouraoui wrote a diary that resembles her. Poupée Bella has the characteristics of a diary, but also those of an autobiographical narrative. We can also find in it some traces of a testimony. What is certain is it belongs to the sphere of “self-narrative”, and it has an undeniable poetic value that shows the sensitivity of the author and her true love for writing.